Urbanization and Farm Size Changes: Implications for Livestock Research - Haan, Cees de (CGIAR Independent Science and Partnership Council, 2013)
This paper identifies issues for livestock research emerging from urbanization and changing farm size in Sub-Saharan Africa and Asia. It highlights the strong past and the expected, although somewhat slower, continuing demand for livestock source food in the developing world.